Influence of short-term sampling parameters on the uncertainty of the Lden environmental noise indicator. (16th February 2015) - Mateus, M; Carrilho, J Dias; da Silva, M Gameiro
Abstract: The present study deals with the influence of the sampling parameters on the uncertainty of noise equivalent level in environmental noise measurements. The study has been carried out through the test of different sampling strategies doing resampling trials over continuous monitoring noise files obtained previously in an urban location in the city of Coimbra, in Portugal. On short term measurements, not only the duration of the sampling episodes but also its number have influence on the uncertainty of the result. This influence is higher for the time periods where sound levels suffer a greater variation, such as during the night period. In this period, in case both parameters (duration and number of sampling episodes) are not carefully selected, the uncertainty level can reach too high values contributing to a loss of precision of the measurements. With the obtained data it was investigated the sampling parameters influence on the long term noise indicator uncertainty, calculated according the Draft 1st CD ISO 1996-2:2012 proposed method. It has been verified that this method allows the possibility of defining a general methodology which enables the setting of the parameters once the precision level is fixed. For the three reference periods defined for environmental noise (day, evening and night), it was possible to derive a two variable power law representing the uncertainty of the determined values as a function of the two sampling parameters: duration of sampling episode and number of episodes.